Evaluation of Sucrose for In Vitro Germination and Growth of the Entomopathogenic Fungus Beauveria bassiana (BALSAMO) VUILLEMIN and Paecilomyces sp. (DEUTEROMYCETES, MONILIALES) - Aminudin Afandhi; Siti Rasminah Chailani; Agustiawati Agustiawati (University of Brawijaya, 2012)
AbstractIn order to examine some possible effects of granulated sugar and sucrose in B. bassiana conidiasuspension, we examined the effects of sucrose on germination dan growth of Beauveria bassiana and Paecilomyces sp. in vitro. We hoped to provide some information relevant to mass production methods for B. bassiana and Paecilomyces sp. The conidia germination and growth of B. bassiana and Paecilomyces sp. were increased by addition of sucrose in medium. The addition sucrose maybe a useful carbohydrate source for use in mass production and carrier ingredient into conidiasuspension as bioinsecticide.Keywords: Beauveria bassiana, Paecilomyces sp., conidia germination, mycelial growth, sucrose